(untitled) (Fiep Bulletin - online, 2014)
This study addresses the Paralympic swimming that through government, private incentives and social projects is growing and attracting the growing interest of new practitioners and professionals from diverse fields. The present study aimed to analyze the level of satisfaction and self-perceived body image of athletes with physical disabilities. The type of study is descriptive with quantitative and qualitative nature, where seven athletes belonging to the staff of High Yield PFDA Paralympic swimming in the survey. Data were collected before and during training conducted in SESI - Club Partnership through Dysmorphic Disorders Questionnaire and the Cooper test adapted to swimming which was held in a 25 meter pool. The results showed that athletes with disabilities team have satisfactory levels of physical fitness and do not reflect the degree of dissatisfaction with their appearance. It was concluded by correlating levels of fitness with body image of Paralympic athletes swimming the limitations caused by physical disability are not seen by them, but rather that its potentialities are developed and refined by the modality.